Um arcabouço para otimizações em máquinas de estado abstratas - Kristian Magnani dos Santos (2006)
The Abstract State Machines methodology oers a powerful, easy-to-use mechanism to formally specify the semantics of algorithms. The k`ar framework adds to it optimization capability, allowing the transformation of ASM specications into ecient programs, which isimportant in order to use the specications as realistic programs. Moreover, the optimizations are modules to be plugged-in on the y, so that independent developers can build their own optimizations without concerning about the internal details of the k`ar framework. Finally,the wide set of constructions of the language understood by the framework allows its use as a target for compilers aiming the ASM methodology.